2017
DOI: 10.1002/ijc.31189
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation‐based biological aging and cancer risk and survival: Pooled analysis of seven prospective studies

Abstract: The association between aging and cancer is complex. Recent studies have developed measures of biological aging based on DNA methylation and called them "age acceleration." We aimed to assess the associations of age acceleration with risk of and survival from seven common cancers. Seven case-control studies of DNA methylation and colorectal, gastric, kidney, lung, prostate and urothelial cancer and B-cell lymphoma nested in the Melbourne Collaborative Cohort Study were conducted. Cancer cases, vital status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
176
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(192 citation statements)
references
References 69 publications
(153 reference statements)
14
176
2
Order By: Relevance
“…All MCCS participants were of European descent, including 25% born in Italy or Greece. Blood DNA methylation was measured for 6,404 participants in one of six nested case‐control studies for breast cancer, colorectal cancer, mature B‐cell neoplasms, urothelial cell carcinoma, kidney cancer, or lung cancer . In the breast cancer study, only women who were included as controls were selected, to avoid the possibility of collider bias .…”
Section: Methodsmentioning
confidence: 99%
“…All MCCS participants were of European descent, including 25% born in Italy or Greece. Blood DNA methylation was measured for 6,404 participants in one of six nested case‐control studies for breast cancer, colorectal cancer, mature B‐cell neoplasms, urothelial cell carcinoma, kidney cancer, or lung cancer . In the breast cancer study, only women who were included as controls were selected, to avoid the possibility of collider bias .…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, DNA methylation was a research hotspot about cancer including renal cancers. The heterogeneity of DNA methylation was observed by Dugué et al, with stronger associations for risk of kidney cancer . Additionally, Kumar et al put forward the hypothesis that IQGAP2 and IQGAP3 were promised to be prognosis therapeutic target of specific cancers including renal cancer for the close connection of their methylation and cancers .…”
Section: Discussionmentioning
confidence: 97%
“…H, The apoptosis cells were increased in 5-Aza-dC treatment group and TSA treatment group and co-treatment group displayed more obvious trend (×40) | 6655 LI and YU showed that 5-Aza-dC and TSA could better block the tumour growth. 26 Additionally, Kumar et al put forward the hypothesis that IQGAP2 and IQGAP3 were promised to be prognosis therapeutic target of specific cancers including renal cancer for the close connection of their methylation and cancers. 27 It also reports that RPS6KA4/MIR1237 and AURKC promoter regions are differentially methylated in Wilms' tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the critical elements responsible for the loss of epigenetic surveillance is important for understanding the impact of CpG mutations, polymorphisms, and changes in their surrounding sequences and for designing appropriate diagnostic tools. A better understanding of the mechanisms underlying these processes will also help us identify the environmental factors that play a regulatory role in formulating our epigenome [11,47,48] and their effects on epigenetic heredity [49]. Moreover, it improves our understanding of the splicing and alternative splicing processes, which are still poorly understood [5052].…”
Section: Discussionmentioning
confidence: 99%